2020
DOI: 10.1186/s12903-020-01099-2
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic incisor retraction caused changes in the soft tissue chin area: a retrospective study

Abstract: Background: To investigate the area and morphological changes around the soft tissue chin after orthodontic incisor retraction. Methods: Fifty-nine female adults with bimaxillary protrusion requiring extraction of four premolars were included in the study. Cephalograms were taken before (T0) and after (T1) orthodontic treatment. The soft tissue changes, including the area, thickness and morphology were measured. Paired-t tests were performed for statistical comparisons. Pearson correlation analyses and backwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
1
8
0
3
Order By: Relevance
“…Additionally, soft tissues around the chin region and upper lip thickness have been reported to be relatively stable. 2 , 29 In this study, Pearson correlation analysis showed that variables associated with ideal maxillary incisor position generally showed strong correlations with nose and chin morphology. The distances of U1-APog, U1-Ap, U1-NA, U1-NPog, and U1-Sn vert positively correlated with the prominence of the nose; moreover, U1-APog distance, U1-Np, and U1-Sn vert showed positive correlations with soft tissue chin thickness.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Additionally, soft tissues around the chin region and upper lip thickness have been reported to be relatively stable. 2 , 29 In this study, Pearson correlation analysis showed that variables associated with ideal maxillary incisor position generally showed strong correlations with nose and chin morphology. The distances of U1-APog, U1-Ap, U1-NA, U1-NPog, and U1-Sn vert positively correlated with the prominence of the nose; moreover, U1-APog distance, U1-Np, and U1-Sn vert showed positive correlations with soft tissue chin thickness.…”
Section: Discussionmentioning
confidence: 52%
“… 1 In particular, the sagittal position and inclination of the incisors are highly relevant to lip and chin prominence. 1 , 2 Thus, orthodontists must determine the ideal position of the incisors when formulating the treatment plan, selecting the extraction vs. non-extraction approach, and adopting an anchorage design.…”
Section: Introductionmentioning
confidence: 99%
“…Convex deformity has always been a problem that concerns some Chinese adults a lot [ 42 , 43 ]. Adult patients with convex deformity, mainly aged from 18 to 40, have high treatment expectations, demanding the most retraction to achieve a straight profile [ 44 , 45 ]. The typical orthodontic treatment is the anterior teeth retraction after the extraction of first premolars [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Різні частини обличчя, включаючи морфологію чола, носа, підборіддя та положення губ, повинні бути гармонійно скоординовані для досягнення привабливості обличчя. Окрім суб'єктивної оцінки фотографій, ортодонти також покладаються на впровадження об'єктивних вимірювань телерентгенограм в бічній проекції, щоб скласти план лікування та оцінити результати лікування [1,5,2,7].…”
Section: вступunclassified